How to measure monotony-related fatigue? A systematic review of fatigue measurement methods for use on driving tests. (2nd January 2020) - Bier, Lukas; Wolf, Philipp; Hilsenbek, Hanna; Abendroth, Bettina
Abstract: The aim of this study is to identify suitable science-based methods for measuring monotony-related fatigue. Monotony is one of three causes of fatigue that to date has rarely been considered in isolation. With an ongoing automation of the driving task the drivers monotony will drastically increase in the future. The methods used, such as the questions asked in interviews, can influence and distort the monotony experienced by subjects during driving tests. For this reason, not all measurement methods generally used to measure fatigue can be used when studying the role of monotony. A systematic literature search based on previously defined criteria allowed us to identify 53 publications which adequately described and evaluated the measurement methodology used to measure fatigue. The result was a list of 25 methods used in the 53 studies that we analysed. These include studies of drivers' condition data and data about their performance. The measurement methods were evaluated based on the evaluations published by the authors who used each method. Further the methods influence on a monotonous study design was critically discussed by the authors of this paper. The paper concludes with a derived measurement concept for simulated driving tests. This work supports future research teams in the selection of a suitable measurement concept for investigating monotony related fatigue and appropriate countermeasures.